ANALISIS KEWENANGAN MAHKAMAH KONSTITUSI DALAM PENYELESAIAN SENGKETA KEWENANGAN LEMBAGA NEGARA - Femmie Cynthia; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
One of the authorities of the Constitutional Court based on Article 24C Paragraph 1 of the 1945Constitution is regarding the settlement of disputes over the authority of state institutions. However,not all state institutions in dispute can be resolved in the Constitutional Court. The purpose of thispaper is to analyze how the authority of the Constitutional Court is in resolving disputes over theauthority of state institutions and how it relates to dispute resolution on the authority of independentstate institutions. The research method used is legal research method with data collection techniques,namely based on legal literature related to the object of research. The legal materials used in thispaper are taken from primary legal materials in the form of legal norms or rules or statutoryprovisions as well as secondary legal materials such as books and related legal journals. TheConstitutional Court here in examining, adjudicating, and deciding a dispute on the authority of stateinstitutions considers the provisions or conditions related to subjectum litis and objectum litis. Thenbased on cases that occurred in Indonesia related to state institutions that can be applicants anddefendants in disputes over the authority of constitutional institutions are not only limited to the mainstate institutions, but other independent institutions whose authorities are regulated in theConstitution. Then only independent state institutions that have constitutional authority or areregulated in the 1945 Constitution can be resolved in the Constitutional Court.